The Influence Of Sharia Insurance Education Through Social Media And The Role Of Ulama On Increasing Public Awareness Of Sharia Insurance - Nur Ajizah Harahap; Rahmi Syahriza; Marliyah Marliyah (JURNAL ECONOMINA, 2026)
Although the Islamic insurance industry in Indonesia shows positive developments, the level of public awareness in using Islamic insurance products is still relatively low. This condition indicates that efforts to increase public knowledge, understanding, and trust in Islamic insurance still need to be optimized. This study aims to analyze the effect of Islamic Insurance Education through Social Media and the Role of Ulama on Public Awareness in Islamic Insurance in Medan City. The research data was obtained through questionnaires and analyzed using SPSS version 30 with validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, partial tests (t-test), simultaneous tests (F-test), and coefficient of determination tests. The results show that Islamic Insurance Education through Social Media has a positive and significant effect on Public Awareness in Islamic Insurance (β = 0.491; p = 0.003). In addition, the Role of Ulama also has a positive and significant effect with a more dominant contribution (β = 0.919; p = 0.000). Simultaneously, both variables had a positive and significant effect on Public Awareness (F = 56.667; p = 0.000).Two independent variables explain 52.9% of the variation in public awareness, while the remaining 47.1% is influenced by factors not included in the research model, based on an *Adjusted R-squared* value of 0.529. This finding indicates that the synergy between education through social media and the role of religious scholars is an effective strategy in increasing public awareness, understanding, and trust in Islamic insurance. Keywords: Social Media Education, Role of Religious Scholars, Public Awareness, Islamic Insurance